2015
DOI: 10.3897/zookeys.524.5951
|View full text |Cite
|
Sign up to set email alerts
|

Immatures of the New World treehopper tribe Amastrini (Hemiptera, Membracidae, Smiliinae) with a key to genera

Abstract: The immatures stages of 8 of the 11 genera (Amastris Stål, Bajulata Ball, Erosne Stål, Harmonides Kirkaldy, Idioderma Van Duzee, Neotynelia Creão-Duarte & Sakakibara, Tynelia Stål, and Vanduzea Goding) of the tribe Amastrini are described for the first time along with brief diagnoses of Membracidae and the subfamily Smiliinae. A key to genera and notes on biology are provided. Multiple species of most genera are illustrated. Based on its distinct nymphal morphology, Vanduzea laeta nolina Ball is elevated to sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
(21 reference statements)
0
10
2
Order By: Relevance
“…Quisenberry et al (1978) found distinguishing features for Acutalis, which is the only acutaline genus represented in Missouri, and those features were sufficient for that fauna. Considered within the larger context of Smiliinae, those features also apply to the Amastrini genera Bajulata Ball, Erosne Stål, Harmonides Kirkaldy, and some Amastris Stål (McKamey et al 2015). But these features do not apply to the acutaline genera Bordoniana, which has abdominal scoli directed dorsally, or Thrasymedes, which has scoli on the head and pronotum, or even some other Acutalis, which have scoli on the head (1 pair) and pronotum (2 pairs) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quisenberry et al (1978) found distinguishing features for Acutalis, which is the only acutaline genus represented in Missouri, and those features were sufficient for that fauna. Considered within the larger context of Smiliinae, those features also apply to the Amastrini genera Bajulata Ball, Erosne Stål, Harmonides Kirkaldy, and some Amastris Stål (McKamey et al 2015). But these features do not apply to the acutaline genera Bordoniana, which has abdominal scoli directed dorsally, or Thrasymedes, which has scoli on the head and pronotum, or even some other Acutalis, which have scoli on the head (1 pair) and pronotum (2 pairs) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The present paper is part of the larger effort to describe the immature stages of New World treehopper genera, which has so far covered the Caribbean genera Antillotolania Ramos, Deiroderes Ramos (McKamey and Brodbeck 2013), and tribe Quadrinareini (McKamey and Wallner 2022). The nymphs of the continental tribes Amastrini (McKamey et al 2015) and Thuridini (McKamey and Porter 2016), and the membracine genus Eunusa Fonseca (McKamey 1992) have also been described. This work treats two more tribes of the New World subfamily Smiliinae: Acutalini and Micrutalini.…”
Section: Introductionmentioning
confidence: 99%
“…The voucher (INHS) has the label “Immatures Project Voucher, McKamey et al 2015” and the species name.…”
Section: Methodsmentioning
confidence: 99%
“…The terminology, 75 characters and 322 potential character states are the same used for Amastrini (McKamey et al 2015). The character descriptions and data are posted online on the USDA/ARS Systematic Entomology Laboratory website (McKamey 2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation